General Health Benefits and Pharmacological Activities of Triticum aestivum L. - Said Moshawih; Rabi’atul Nur Amalia Abdullah Juperi; Ganesh Sritheran Paneerselvam; Long Chiau Ming; Kai Bin Liew; Bey Hing Goh; Yaser Mohammed Al-Worafi; Chee-Yan Choo; Shobna Thuraisingam; Hui Poh Goh; Nurolaini Kifli (Molecules, 2022)
Common wheat (Triticum aestivum), one of the world’s most consumed cereal grains, is known for its uses in baking and cooking in addition to its medicinal uses. As this plant’s medical benefits are enormous and scattered, this narrative review was aimed at describing the pharmacological activities, phytochemistry, and the nutritional values of Triticum aestivum. It is a good source of dietary fiber, resistant starch, phenolic acids, alkylresorcinols, lignans, and diverse antioxidant compounds such as carotenoids, tocopherols and tocotrienols. These constituents provide Triticum aestivum with a wide range of pharmacological properties, including anticancer, antimicrobial, antidiabetic, hypolipemic, antioxidant, laxative, and moisturizing effects. This review summarized the established benefits of wheat in human health, the mode of action, and different clinical, in vitro and in vivo studies for different varieties and cultivars. This review also gives an insight for future research into the better use of this plant as a functional food. More clinical trials, in vivo and in vitro studies are warranted to broaden the knowledge about the effect of Triticum aestivum on nutrition-related diseases prevention, and physical and mental well-being sustenance.